Silent parade - Higashino, Keigo, 1958- (Higashino, Keigo, 1958- Detective Galileo novels., 2021)
"Detective Galileo, Keigo Higashino's best loved character from The Devotion of Suspect X, returns in Silent Parade, a complex and challenging mystery-several murders, decades apart, with no solid evidence. A popular young girl disappears without a trace, her skeletal remains discovered three years later in the ashes of a burned out house. There's a suspect and compelling circumstantial evidence of his guilt, but no concrete proof. When he isn't indicted, he returns to mock the girl's family. And this isn't the first time he's been suspected of the murder of a young girl, nearly twenty years ago he was tried and released due to lack of evidence. Chief Inspector Kusanagi of the Homicide Division of the Tokyo Police worked both cases. The neighborhood in which the murdered girl lived is famous for an annual street festival, featuring a parade with entries from around Tokyo and Japan. During the parade, the suspected killer dies unexpectedly. His death is suspiciously convenient but the people with all the best motives have rock solid alibis. CI Kusanagi turns once again to his college friend, Physics professor and occasional police consultant Manabu Yukawa, known as Detective Galileo, to help solve the string of impossible-to-prove murders"--